The derealization of the old city in the ideal city - Costa, Erika Bataglia da (Revista Archai, 2010)
In this study we intend to investigate the ancient city as the state unable to guarantee the protection and enforcement of justice between individuals and the birth of the Republic undemocratic libel resultant of the failure and the decay of the old city. Plato tries to convince men that it is life in a community that makes it possible to happiness in our short roaming in the world. The ontology of the property falls here as a strategy of persuasion on the insistence of preserving the unity of the city as institutional correlate the individual’s fully integrated itself.